2013
DOI: 10.1038/srep02086
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing graphene reinforcing potential in composites by hydrogen passivation induced dispersion

Abstract: To take full advantages of the structural uniqueness and exceptional properties of graphene as reinforcement in composites, harvesting well-dispersed graphene is essential. On the other hand, it is challenging to achieve simultaneously high stiffness, strength and toughness in engineered materials because of the trade-off relations between these properties. Here we demonstrate that the graphene reinforcing potential can be significantly enhanced through the excellent dispersion of graphene sheets in the matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 48 publications
3
69
0
1
Order By: Relevance
“…17 It has recently been demonstrated that both surface chemistry and size of graphene platelets play a key role in the toxicity, distribution, and excretion of graphene and that, therefore, different graphene materials may have different influences on the organism. 18 GO is well dispersed in water while rGO is hydrophobic, often creating agglomerates in water. The formation annexin V-alexa Fluor ® 488 and PI assay analysis.…”
Section: Discussionmentioning
confidence: 99%
“…17 It has recently been demonstrated that both surface chemistry and size of graphene platelets play a key role in the toxicity, distribution, and excretion of graphene and that, therefore, different graphene materials may have different influences on the organism. 18 GO is well dispersed in water while rGO is hydrophobic, often creating agglomerates in water. The formation annexin V-alexa Fluor ® 488 and PI assay analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the likely aggregation of graphene due to their strong hydrophobicity and van der Waal's attraction at higher loading could have also affected the resulting viscosity and morphology of the membrane. The van der Waal's interacted between each graphene nanoparticles and the C -C bonds by jointing C dangling bonds of other graphene nanoparticles [29]. Thus, the more tendency of graphene to aggregate at higher loadings (0.7 to 2.0 wt%) resulted to the decrease in pore sizes.…”
Section: Evaluation Of Membrane Performance By Agmdmentioning
confidence: 99%
“…Graphene also attracts great attention as the strengthening component in composites [5][6][7] . Characterization of the mechanical properties of graphene is essential both from a technological perspective for its reliable applications and from a fundamental interest in understanding its deformation physics 8,9 .…”
mentioning
confidence: 99%